2011
DOI: 10.1590/s0104-11692011000300018
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and the collective care practices within the family health strategy: salud de la familia

Abstract: This qualitative study identifies and analyzes the practices of nurses regarding collective care interventions in the context of the Family Health Strategy (FHS) and its knowledge development. Semi-structured interviews were held with nurses working in the FHS and thematic analysis was used to analyze data. The theoretical framework was based on the theories of institutional analysis and work processes. The results are arranged into two main themes: Conceptions that support collective care practices and Practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
0
14
0
3
Order By: Relevance
“…Thus, the family unit has, throughout the years, suffered transformations, mainly in the way of transmitting values on subjects connected to STD/HIV (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the family unit has, throughout the years, suffered transformations, mainly in the way of transmitting values on subjects connected to STD/HIV (2) .…”
Section: Introductionmentioning
confidence: 99%
“…This seemed to us to be another important factor, as there is a naturalization of making educational groups as being restricted to face-to-face meeting, neglecting their planning and evaluation (7) . However, we highlight the advantages towards the possibility that professionals with diverse backgrounds can work together in educational groups composing a multi-professional work, desirable in the family health strategy (4,7,10) .…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, some authors (2)(3)(4)(5)(6)(7) point out that, traditionally, in these educational groups, there is a predominance of information being provided, focusing on pathologies, with the predominance of traditional pedagogical conceptions being transmitted in a vertical form, weakening the integration and collective discussion. In general, they are also well developed with few material conditions and management support (6) .…”
Section: Introductionmentioning
confidence: 99%
“…When studies have shown that the main referential adopted for conducting groups is still that in which the individuals participate in meeting to acquire knowledge and change their manner of living into that which, for the team, is not healthy or may cause damage (23) , it is clear that by means of music it is possible to innovate the educational activity in groups, in agreement with the conservative practices that are still prevalent.…”
Section: Discussionmentioning
confidence: 99%